(untitled) (Journal of Oriental Studies, 2025)
The current period of political processes in a number of countries in Europe and Asia is characterized by the growing influence of radical right-wing parties. The issue of differences and similarities of European far-right nationalists has been actively discussed, but a broader approach to the study of the phenomenon is urgent. Far-right nationalism in France and Japan, due to historical, cultural, political, and social characteristics, differs from each other in its genesis, ideological accents, social base, and cultural and political aspects. Far-right ideology, regardless of the country, is similar in ethnocentrism, striving for cultural homogeneity, xenophobia, opposition to immigration, commitment to traditional values, and a tendency toward authoritarianism. The paper analyzes the similarities and differences of far-right nationalism in different parts of Eurasia in the current period of volatility of globalization and the aggravation of geopolitical and geo-economic contradictions. Its novelty lies in the analysis of the latest studies of far-right nationalism and forecasting the consequences of its strengthening on a national and global scale. The key concepts of the study were the theories of comparative nationalism, political realism, far-right populism, ethnic exceptionalism, post -colonialism and identity. In the writing of article is used the synergetic of comparative studies, historical-contextual, ideological discourse analysis, political -sociological and cultural -anthropological methods. The results of the study allowed us to identify the similarities and differences of far-right nationalism in France and Japan, which contributes to understanding the overall picture of the unity and diversity of the far-right part of the political spectrum: parties, movements and their leaders. Keywords: far right, nationalism, France, Japan, ethno nationalism, militarism, authoritarianism